From Polyclonal Sera to Recombinant Antibodies: A Review of Immunological Detection of Gluten in Foodstuff - Eduardo Garcia-Calvo; Aina García-García; Raquel Madrid; Rosario Martin; Teresa García (Foods, 2020)
Gluten is the ethanol-soluble protein fraction of cereal endosperms like wheat, rye, and barley. It is widely used in the food industry because of the physical–chemical properties it gives to dough. Nevertheless, there are some gluten-related diseases that are presenting increasing prevalences, e.g., celiac disease, for which a strict gluten-free diet is the best treatment. Due to this situation, gluten labeling legislation has been developed in several countries around the world. This article reviews the gluten immune detection systems that have been applied to comply with such regulations. These systems have followed the development of antibody biotechnology, which comprise three major methodologies: polyclonal antibodies, monoclonal antibodies (mAbs) derived from hybridoma cells (some examples are 401.21, R5, G12, and α-20 antibodies), and the most recent methodology of recombinant antibodies. Initially, the main objective was the consecution of new high-affinity antibodies, resulting in low detection and quantification limits that are mainly achieved with the R5 mAb (the gold standard for gluten detection). Increasing knowledge about the causes of gluten-related diseases has increased the complexity of research in this field, with current efforts not only focusing on the development of more specific and sensitive systems for gluten but also the detection of protein motifs related to pathogenicity. New tools based on recombinant antibodies will provide adequate safety and traceability methodologies to meet the increasing market demand for gluten-free products.